Instrumental characterization of banana dessert gels for the elderly with dysphagia - Kamonwan Suebsaen (2020)
© 2019 Elsevier Ltd Fruit gels are common dessert easily consumed by the elderly. It can be an alternative food that provides essential nutrition for the elderly with dysphagia (ED). Soft-textured banana dessert gels with various gel hardness (10, 15, and 20 kPa) were prepared using different hydrocolloids (agar, carrageenan, and gelatin). The instrumental rheological and textural properties, and sensory attributes of the gels were investigated. Agar gels showed the lowest elastic behavior (G′ > G″) and was within the safe-swallowable range (tan δ; 0.10–0.13). Agar gels with a hardness of 10 kPa, notable for a soft texture, low texture profile parameters, and low chewing and swallowing counts, were served to 5 ED. The gels were safely eaten, and no choking occurred. The high positive correlation (r > 0.80) of tan δ with swallowing and hardness scores implied that the ED favored a soft-textured gel. The higher the instrumental texture properties (springiness, cohesiveness, gumminess, and chewiness), the lower the scores for the chewing and swallowing attributes (r > 0.86, p ≤ 0.01), and the greater the chewing and swallowing frequencies (r > 0.82, p ≤ 0.01). Linear regression analysis confirmed significant linear models (p ≤ 0.01, R2 > 0.80) for the cohesiveness, gumminess, and chewiness, and sensory properties of mastication. The results indicated that the instrumental evaluation offers a useful guideline for the food industry to develop products for ED and avoid the risks of doing sensory testing with ED patients.